PERFORMANCE ASSESSMENT OF AN OFF DESIGN AIR FINNED COOLER - SAIPUDDIN, NURAMALINA (IRC, 2016)
Nowadays, the usage of air finned cooler are widely being employed in a wide variety of industry including the oil and gas industry. Corrosion and fouling are factor commonly being relate to the degradation of the heat exchanger performance. These lead the engineers to constantly assess the performance of the heat exchanger. A template is being proposed to ease up the assessment of the heat exchanger performance by relating the performance with the off design parameter of the heat exchanger. This template only limited for the air finned cooler heat exchanger that being used in the oil and gas industry. There are two methods being used in order to assess the performance of air finned cooler which are LMTD method and effectiveness-NTU method. These two methods will be used to obtain more accurate result. The off design parameters that will take into consideration are number of plugged pipe which this factor will affect the formula that will be used in the template. The result show that the number of plugged pipe give significant affect to the efficiency of the air finned cooler. The estimation of the life span of the air finned cooler can be approximately estimated by using this template.